Synergistic effects of dodecane-castor oil acid mixture on the flotation responses of low-rank coal: A combined simulation and experimental study - Fen Xu; Shiwei Wang; Rongjie Kong; Chengyong Wang (International Journal of Mining Science and Technology, 2023)
The utilization of an appropriate collector or surfactant is crucial for the beneficiation of low-rank coal. However, in previous studies, the selection of surfactants was primarily based on flotation procedures, which hinders the understanding of the interaction mechanism between surfactant groups and oxygen-containing functional groups at the surface of low-rank coal. In this study, we investigate the flotation of low-rank coal in the presence of a composite collector by using a combined theoretical and experimental approach. The maximum flotation mass recovery achieved was 82.89% using a 3:1 mixture of dodecane and castor oil acid. Fourier-transform infrared and X-ray photoelectron spectroscopic analyses showed that castor oil acid was effectively adsorbed onto the surface of low-rank coal, enhancing the hydrophobicity of the coal. In addition, the diffusion coefficient of water molecules in the water-composite collector-coal system was greater than that in the dodecane system. Moreover, due to the presence of castor oil acid in the flotation process, the adsorption distance of dodecane and low-rank coal became shorter. Molecular dynamics simulations revealed that the diffusion and interaction of surfactant molecules at the interface of low-rank coal particles and water was enhanced because the adsorption of the dodecane-castor oil acid mixture is primarily controlled by hydrogen bonds and electrostatic attraction. Based on these results, a better surfactant for flotation of low-rank coal is also proposed.